The Crucial Role of the PPAR Signaling Pathway in the Diagnosis and Treatment of Chronic Obstructive Pulmonary Disease: An Analysis of Gene Expression and Macrophage Polarization - Zhang L; Guo R; Wu H; Abudusalamu A; Ding W; Li D; Wei X; Niu L (International Journal of COPD, 2025)
Ling Zhang,* Rong Guo,* Haixia Wu, Abula Abudusalamu, Wei Ding, Dewei Li, Xuemei Wei, Lin Niu Department of Respiratory and Critical Care Medicine, People’s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, 830001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuemei Wei, Department of Respiratory and Critical Care Medicine, People’s Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Tianshan District, Urumqi, 830001, People’s Republic of China, Tel +86-13579846469, Email wu1208522@163.com Lin Niu, Department of Respiratory and Critical Care Medicine, People’s Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Tianshan District, Urumqi, 830001, People’s Republic of China, Tel +86-1319989525, Email 363141843@qq.comPurpose: To explore the role of the peroxisome proliferator-activated receptor (PPAR) signaling pathway in chronic obstructive pulmonary disease (COPD) and identify potential biomarkers and therapeutic targets, given that COPD is a major global health burden and the specific molecular mechanisms of the PPAR pathway in COPD are not fully understood.Patients and Methods: Gene expression data from the GEO database were analyzed to identify key genes and immune cells related to COPD. Peripheral blood samples were collected from COPD patients and healthy controls. Key genes were confirmed by PCR, and immune cells were characterized using flow cytometry.Results: Eight core genes associated with the PPAR signaling pathway were identified. NCOA1 and PPARGC1A were downregulated in COPD patients, while NCOR1, NRIP1, and SLC27A5 were upregulated. Receiver operating characteristic (ROC) curve analysis showed that NCOA1, NCOR1, and SLC27A5 have potential for COPD diagnosis. There was a significant increase in the proportion of M2 macrophages in COPD patients, indicating a shift in macrophage polarization towards the M2 phenotype. Genes within the PPAR signaling pathway were closely associated with macrophage polarization state.Conclusion: The research findings provide new biomarkers and potential therapeutic targets for the early diagnosis and personalized treatment of COPD, emphasizing the significant role of the PPAR signaling pathway in the pathogenesis of COPD.Clinical Trial Registry: The population study involved in this research has been registered under the (chictr.org.cn). Registry identifier: ChiCTR2400086268.Keywords: COPD, PPAR signaling pathway, diagnosis biomarker, macrophage polarization